2003
DOI: 10.1016/s0741-5214(02)75140-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening for asymptomatic internal carotid artery stenosis and aneurysm of the abdominal aorta: comparing the yield between patients with manifest atherosclerosis and patients with risk factors for atherosclerosis only1 1Competition of interest: none.

Abstract: Screening for ICAS should be limited to patients referred with PAD or AAA, especially those with advanced age or with low diastolic blood pressure. Screening for AAA should be limited to patients referred with PAD or with TIA, stroke, or ICAS, particularly those with advanced age or tall stature. In patients referred with angina pectoris or MI and those referred with only risk factors for atherosclerosis, screening cannot be endorsed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(61 citation statements)
references
References 44 publications
1
59
1
Order By: Relevance
“…This finding is in contrast to that of previous studies disclosing a prevalence of greater than 70% carotid stenosis ranging 5%-24% in patients suffering from peripheral vascular disease. [4][5][6]8,[17][18][19][20][21][22][23] In a meta-analysis of nineteen studies, Ahmed and Al-Khaffaf concluded that prevalence of .70% asymptomatic carotid artery stenosis was 14% in patients with peripheral vascular disease. 7 This discrepancy may be explained by the fact that asymptomatic significant carotid stenosis occurs in elderly patients (age $ 65 years) with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is in contrast to that of previous studies disclosing a prevalence of greater than 70% carotid stenosis ranging 5%-24% in patients suffering from peripheral vascular disease. [4][5][6]8,[17][18][19][20][21][22][23] In a meta-analysis of nineteen studies, Ahmed and Al-Khaffaf concluded that prevalence of .70% asymptomatic carotid artery stenosis was 14% in patients with peripheral vascular disease. 7 This discrepancy may be explained by the fact that asymptomatic significant carotid stenosis occurs in elderly patients (age $ 65 years) with peripheral vascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…4,17,20 In contrast, the majority of the previous studies found a link between age, as a predicting risk factor, and asymptomatic significant carotid artery stenosis. 5,6,8,21,23,27,28 Alexandrova et al found significant correlations between all risk factors (sex, age, diabetes mellitus, smoking, and hypertension) and the disease severity. 5 Simons et al 28 and Kurvers et al 23 indicated a significant association between low diastolic blood pressure and carotid artery stenosis.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…the best predictors for detecting an aaa were male gender, advanced age (>65 years), and a history of smoking. 65 in the sMart study, 55 the prevalence of an aaa 3 cm or larger is low in patients with risk factors for atherosclerosis only (0.4-1.6%), intermediate in patients with angina pectoris or Mi (2.6%), and highest in patients with Pad (6.5%) or transient ischemic attack (tia), stroke, or iCa stenosis (6.5%). selecting patients with advanced age increased the prevalence of aaa 3 cm or larger to 9.6%.…”
Section: Renal Artery Diseasementioning
confidence: 97%
“…since Pad patients have an increased risk of stroke, it might be reasonable to screen those patients for carotid artery disease routinely. in the sMart study, 55 the prevalence of internal carotid artery (iCa) stenosis 70% or greater was low in patients with risk factors for atherosclerosis only (1.8-2.3%), intermediate in patients with angina pectoris or Mi (3.1%), and highest in patients with Pad (12.5%) or abdominal aortic aneurysm (aaa) (8.8%). in patients with Pad, selecting those ages 55 years and older increased the prevalence of iCa stenosis to 21.8%.…”
mentioning
confidence: 98%